The Role of the Knowledge Economy in Developing the Export Sector in the Kingdom of Saudi Arabia During the Period (2000-2021) - Khayat, Sahar Hassan; AlAmri, Ghadah Muhammed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to examine the impact of the knowledge economy on the export sector in Saudi Arabia during the period from 2000 to 2021, due to the accelerating pace of global developments in the economic field. The knowledge economy has become a crucial factor in shaping the global economy. From this standpoint, it has become necessary to assess the impact of various knowledge indicators on exports and economic growth in Saudi Arabia. This impact was measured through the use of descriptive analytical methods, in addition to econometric methods and time series data for all study variables. The dependent variable was total exports, while the independent variables included exports of goods and information and communications technology (ICT) as a percentage of total goods, internet users as a percentage of the population, net foreign direct investment inflows as a percentage of GDP, and trade openness as a percentage of GDP. The regression model was estimated using the Ordinary Least Squares (OLS) method, relying on the EViews9 program for data analysis and hypothesis testing. The study reached several conclusions, including that increases in ICT exports and foreign direct investment do not significantly impact total exports, but increases in internet users and trade openness positively affect total exports. The study also recommended the development of digital infrastructure and the diversification of the Saudi economy away from dependence on the petrochemical sector, which requires effective economic policies to support the ICT sector. Additionally, the study emphasized the need to stimulate e-commerce and invest in research and development to improve the quality of Saudi products, with a focus on developing effective international marketing strategies targeting knowledge-based and technological sectors.
Keywords: Knowledge Economy; Exports; Information and Communication Technology